(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2021)
Potato is an important vegetable crop of Bangladesh which is facing challenges worldwide due to a quarantine pathogen, Ralstonia solanacearum. It is a very successful bacterial pathogen against most of the traditional management practices. Suspension of ten bioactive compounds viz. propolis, honey, turmeric powder+oil, turmeric powder, magnesium chloride, boiled rice fluid, boiled rice fluid+iodine, sun dried cow dung powder, honey+iodine and sodium bicarbonate were evaluated and compared with control (sterile water), commercial bactericide (Krosin AG) and farmers practice (stable bleaching powder). In vitro assessment was done by comparing the inhibition zones produced on TZC (tetrazolium chloride) solid medium in disc diffusion method. All of those compounds produced larger inhibition zones as compared to control which indicated the effectiveness of the test compounds against the bacteria. To screen out the performances of those compounds in vivo, potato seedlings were inoculated in sterilized soil by soil soak method. Later, mature plants were inoculated in unsterilized soil to find the better resulting compound(s) in field soil condition against the disease. Finally, suspension of cow dung (@25%), propolis (@ 6mg/ml) and turmeric powder (@25%) were selected for trial as soil and seed treatment against the pathogen. It was found that, cow dung reduced 28.89% disease severity index which was followed by 26.67% in propolis and 22.22% in turmeric powder as compared to control (84.44%) in artificially inoculated potato plants against R. solanacearum. J. Biodivers. Conserv. Bioresour. Manag. 2020, 6(1): 65-76